SOME SOLUBLE MODELS FOR PERIODIC DECAY AND REVIVAL - Sukumar, C; Buck, B (1984)
The authors present three analytically tractable models for a two-level atom interacting with a coherent or thermal radiation field and study the behaviour of the atomic excitation energy for various initial conditions.